Correction: Multi-functional switches of ditopic ligands with azobenzene central bridges at a molecular scale. Issue 2 (17th December 2019) - Hnid, Imen; Sun, Xiaonan; Frath, Denis; Lafolet, Frédéric; Lacroix, Jean-Christophe
Abstract : Correction for 'Multi-functional switches of ditopic ligands with azobenzene central bridges at a molecular scale' by Imen Hnid et al., Nanoscale, 2019, 11, 23042–23048.